Accumulating Evidence for Axonal Translation in Neuronal Homeostasis - Spaulding, Emily L.; Burgess, Robert W. (Frontiers in Neuroscience, 2017)
The specialized structure of the neuron requires that homeostasis is sustained over the meter or more that may separate a cell body from its axonal terminus. Given this impressive distance and an axonal volume that is many times that of the cell body, how is such a compartment grown during development, re-grown after injury, and maintained throughout adulthood? While early answers to these questions focused on the local environment or the cell soma as supplying the needs of the axon, it is now well-established that the axon has some unique needs that can only be met from within. Decades of research have revealed local translation as an indispensable mechanism of axonal homeostasis during development and regeneration in both invertebrates and vertebrates. In contrast, the extent to which the adult, mammalian axonal proteome is maintained through local translation remains unclear and controversial. This mini-review aims to highlight important experiments that have helped to shape the field of axonal translation, to discuss conceptual arguments and recent evidence that supports local translation as important to the maintenance of adult axons, and to suggest experimental approaches that have the potential to further illuminate the role of axonal translation in neuronal homeostasis.